2017
DOI: 10.1111/odi.12790
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber diameter assessment in cleft lip using image processing

Abstract: The image processing on FFPE tissues resulted in easy quantification of MFD with finding of a smaller MFD on the medial side in males suggesting possible differences in orbicularis oris (OO) muscle between the two sexes in CL that warrants replication using larger number of cases. Moreover, this finding can aid subclinical phenotyping and potentially in the restoration of the anatomy and function of the upper lip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Among environmental factors, tobacco smoking has been found to influence facial morphology (Xuan et al, 2016), and is reported to be the most consistent and strongest risk factor for OFCs (Raut et al, 2019). Such perturbation of the early life environment affects developmental programming in the embryo, with sustained changes potentially detectable in tissues from medial nasal and maxillary sides of the upper lip in cases with nonsyndromic cleft lip with or without cleft palate (nsCL/P) as observed by our group in recent studies (Khan, Little, Abelli, et al, 2018;Khan, Little, Mossey, Steegers-Theunissen, Autelitano, et al, 2018;Khan, Little, Aleotti, et al, 2019;Khan, Little, Nag, et al, 2019).…”
Section: Introductionsupporting
confidence: 62%
“…Among environmental factors, tobacco smoking has been found to influence facial morphology (Xuan et al, 2016), and is reported to be the most consistent and strongest risk factor for OFCs (Raut et al, 2019). Such perturbation of the early life environment affects developmental programming in the embryo, with sustained changes potentially detectable in tissues from medial nasal and maxillary sides of the upper lip in cases with nonsyndromic cleft lip with or without cleft palate (nsCL/P) as observed by our group in recent studies (Khan, Little, Abelli, et al, 2018;Khan, Little, Mossey, Steegers-Theunissen, Autelitano, et al, 2018;Khan, Little, Aleotti, et al, 2019;Khan, Little, Nag, et al, 2019).…”
Section: Introductionsupporting
confidence: 62%
“…Some empirical evidence of reduced proliferation and migration of these mesenchymal cells particularly affected on the medial side is shown in a separate animal study (Everson et al, ). Moreover, these mesenchymal cells eventually form the continuous bands of the future orbicularis oris muscle (Lazzeri et al, ), which is shown to have altered diameter (Khan et al, ; Khan, Little, Abelli, Mossey, et al, ; Khan, Little, Mossey, Steegers‐Theunissen, Bonsi, et al, ) and arrangement (Wijayaweera, Amaratunga, & Angunawela, ) across the two sides in CL cases. Notably, collagen and muscles share structural–functional relationship to ensure proper alignment (Calvi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The average age of cases at the time of first lip surgery was eight months (95% CI 4.6–11.4). The samples were collected at the Regional Centre for Orofacial Clefts and Craniofacial Anomalies, San Paolo Hospital, Milan, Italy in the framework of the PENTACLEFT project (Khan et al, ; Khan, Little, Abelli, Mossey, et al, ; Khan, Little, Mossey, Steegers‐Theunissen, Bonsi, et al, ), which was approved by local IRB (prot. N.08‐2011).…”
Section: Methodsmentioning
confidence: 99%